Stabilizing High Density Cu Active Sites with ZrO2 Quantum Dots as Chemical Ligand in N‐doped Porous Carbon Nanofibers for Efficient ORR. Issue 15 (11th January 2023) - Qiao, Yue; Zhang, Yuanyuan; Xia, Shuhui; Wei, Chaolong; Chen, Yuehui; Chen, Shuo; Yan, Jianhua
Abstract: The emerging transition metal‐nitrogen‐carbon (MNC) materials are considered as a promising oxygen reduction reaction (ORR) catalyst system to substitute expensive Pt/C catalysts due to their high surface area and potential high catalytic activity. However, MNC catalysts are easy to be attacked by the ORR byproducts that easily lead to the deactivation of metal active sites. Moreover, a high metal loading affects the mass transfer and stability, but a low loading delivers inferior catalytic activity. Here, a new strategy of designing ZrO2 quantum dots and N‐complex as dual chemical ligands in N‐doped bubble‐like porous carbon nanofibers (N‐BPCNFs) to stabilize copper (Cu) by forming CuZrO3‐x /ZrO2 heterostructures and CuN ligands with a high loading of 40.5 wt.% is reported. While the highly porous architecture design of N‐BPCNFs builds a large solidelectrolytegas phase interface and promotes mass transfer. The preliminary results show that the half‐wave potential of the catalyst reaches 0.856 V, and only decreases 0.026 V after 10 000 cycles, exhibiting excellent stability. The proposed strategy of stabilizing metal active sites with both heterostructures and CuN ligands is feasible and scalable for developing high metal loading ORR catalyst. Abstract : A strategy of constructing high density but dispersed ZrO2 quantum dots into N‐doped bubble‐like porous carbon nanofibers as the local coordination environment to stabilize copper (Cu) active sites is proposed as the oxygen reduction reaction catalyst. The new catalyst that contains active CuZrO3‐x /ZrO2 heterostructures and CuNC sites exhibits a 4e transfer mechanism and a high half‐wave potential of 0.856 V and delivers.